La protección jurídica de las personas trans a la luz del nuevo escenario normativo en España (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The study of transsexuality requires an interdisciplinary approach, not only from a legal point of view, but also with the contribution of other disciplines such as medicine, psychology, sociology, ethics and philosophy. This is without forgetting the fact that it has been the subject of intense political debate, with the consequent legal fluctuations that this problem has experienced. This contribution aims to analyse the legal situation following the approval of the recent Law 4/2023, of 28 February, for the real and effective equality of trans people and for the guarantee of the rights of LGTBI people.
Keywords: Transsexualism; Gender Identity; Health System; Human Rights; Discrimination; Spain